Factors Affecting Soil Fauna Feeding Activity in a Fragmented Lowland Temperate Deciduous Woodland - Simpson, Jake E.; Slade, Eleanor; Riutta, Terhi; Taylor, Michele E. (PloS one, 2012)
British temperate broadleaf woodlands have been widely fragmented since the advent of modern agriculture and development. As a result, a higher proportion of woodland area is now subject to edge effects which can alter the efficiency of ecosystem functions. These areas are particularly sensitive to drought. Decomposition of detritus and nutrient cycling are driven by soil microbe and fauna coactivity. The bait lamina assay was used to assess soil fauna trophic activity in the upper soil horizons at five sites in Wytham Woods, Oxfordshire: two edge, two intermediate and one core site. Faunal trophic activity was highest in the core of the woodland, and lowest at the edge, which was correlated with a decreasing soil moisture gradient. The efficiency of the assay was tested using four different bait flavours: standardised, ash (Fraxinus excelsior L.), oak (Quercus robur L.), and sycamore (Acer pseudoplatanus L.). The standardised bait proved the most efficient flavour in terms of feeding activity. This study suggests that decomposition and nutrient cycling may be compromised in many of the UK's small, fragmented woodlands in the event of drought or climate change.